2015
DOI: 10.1021/acs.jafc.5b04510
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profile of Salidroside in Rats by Ultraperformance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Mass Spectrometry and High-Performance Liquid Chromatography Coupled with Quadrupole-Linear Ion Trap Mass Spectrometry

Abstract: In the present work, the salidroside metabolite profile in rat urine was investigated, and subsequently the metabolic pathways of salidroside were proposed. After administrations of salidroside at an oral dose of 100 or 500 mg/kg, rat urine samples were collected and pretreated with methanol to precipitate the proteins. The pretreated samples were analyzed by an Acquity ultraperformance liquid chromatography (UPLC) coupled with an HSS T3 column and detected by quadrupole time-of-flight mass spectrometry (Q-TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…administration, whereas it may be further metabolized to other metabolites, and resulted in undetectable p-tyrosol in the plasma sample [138]. The speculation was verified by Hu's experiment, in which 123 and its deglycosylation phase I metabolite p-tyrosol were further metabolized to glucuronidation and sulfation products and mainly excreted through the urine excretion pathway [139]. Later, Guo's research team studied the metabolism of 123 and p-tyrosol in liver tissues after i.v.…”
Section: Pharmacokinetics Of Salidroside (123) and P-tyrosolmentioning
confidence: 98%
See 1 more Smart Citation
“…administration, whereas it may be further metabolized to other metabolites, and resulted in undetectable p-tyrosol in the plasma sample [138]. The speculation was verified by Hu's experiment, in which 123 and its deglycosylation phase I metabolite p-tyrosol were further metabolized to glucuronidation and sulfation products and mainly excreted through the urine excretion pathway [139]. Later, Guo's research team studied the metabolism of 123 and p-tyrosol in liver tissues after i.v.…”
Section: Pharmacokinetics Of Salidroside (123) and P-tyrosolmentioning
confidence: 98%
“…What's more, simultaneous determination of more than one chemical marker and their pharmacokinetic studies were also reported. The microemulsion liquid chromatography (MELC) method [136] and the two-phase hollow fiber liquid phase microextraction coupled with a magnetofluid technique [137] for simultaneous determination of 117, 120, 121 and tubuloside B (139) in rat plasma after oral administration of Cistanche salsa extract by HPLC were developed. In the MELC method, the calibration curve for the four PhGs was linear in the range of 10-1000 ng/mL with the correlation coefficients greater than 0.9994.…”
Section: Pharmacokinetics Of Echinacoside (117) and Acteoside (121)mentioning
confidence: 99%
“…p-Tyrosol sulfate was the predominant metabolite identied in the hepatic metabolism of SAL, which accounted for over 50% of the total metabolites in systemic circulation. 10,11 The formation rate of p-tyrosol sulfate could therefore serve as an indicator for the hepatic metabolic rate of SAL. The liver S9 fraction (RLS) derived from 5 normoxic rats and 5 hypoxic rats were prepared respectively according to previously mentioned method.…”
Section: Assessing the Hepatic Metabolism Of Sal Under Hypoxia And Nomentioning
confidence: 99%
“…7a and b). 10,11 It was noticed that the formations of p-tyrosol sulfate were only dramatically inhibited when SAL was incubated with RLS in the presence of CBG inhibitor, suggesting the potential roles of CBG in the deglycosylation of SAL in rats. Moreover, the formations of p-tyrosol sulfate were signicantly inhibited when p-tyrosol was incubated with RLS in the presence of SULT2A1 inhibitor, suggesting the potential roles of SULT2A1 in the sulfation of SAL in rats.…”
Section: Enhanced Absorption Of Sal In Hypoxicmentioning
confidence: 99%
See 1 more Smart Citation